Simulation Study on Voltage Control for Flexible Neutral Section Passing Based on Line-level Energy Management System - YIN Xiaowei; LI Hongbo; YOU Chuan (Kongzhi Yu Xinxi Jishu)
In order to solve the issue of pantograph arcing on trains passing through neutral sections caused by excessive pressure differentials between both ends of these sections, a safety concern for train operation, this paper presents a voltage control system for flexible neutral section passing based on the line-level energy management system (EMS). The system obtains voltage control commands to control the energy dispatching equipment (EDE) by collecting the status information of the traction network, thereby achieving voltage balance between both ends to ensure smooth passage of trains through neutral sections. This study explored the principle of voltage regulation. A model for EMS voltage regulation was built to simulate the AC power supply system of Chongqing Rail Transit (CRT) Line 15. The simulation revealed that voltage control based on EMS effectively maintained voltage balance by reducing the voltage difference across neutral section ends by more than 20%. This study finding substantiates the efficacy and feasibility of the proposed control system.